2014
DOI: 10.1371/journal.pone.0107172
|View full text |Cite
|
Sign up to set email alerts
|

Do Girls Have a Nutritional Disadvantage Compared with Boys? Statistical Models of Breastfeeding and Food Consumption Inequalities among Indian Siblings

Abstract: BackgroundIndia is the only nation where girls have greater risks of under-5 mortality than boys. We test whether female disadvantage in breastfeeding and food allocation accounts for gender disparities in mortality.Methods and FindingsSecondary, publicly available anonymized and de-identified data were used; no ethics committee review was required. Multivariate regression and Cox models were performed using Round 3 of India’s National Family and Health Survey (2005–2006; response rate = 93.5%). Models were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 24 publications
7
68
0
Order By: Relevance
“…Although inequitable intra‐household food allocation by sex has been noted in South Asian contexts including Nepal, (Harris‐Fry, Shrestha, Costello, & Saville, ), literature on the influence of child sex and feeding of USFB is extremely limited. Fledderjohann et al () found greater consumption of fresh milk by sons as compared with daughters among Indian children below 5 years of age; further exploration of our data showed that male children consumed a higher %TEI‐NBF from healthy snacks than female children, particularly dairy‐based snacks. No studies exploring sex differentials in feeding of USFB to infants and young children have been identified.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Although inequitable intra‐household food allocation by sex has been noted in South Asian contexts including Nepal, (Harris‐Fry, Shrestha, Costello, & Saville, ), literature on the influence of child sex and feeding of USFB is extremely limited. Fledderjohann et al () found greater consumption of fresh milk by sons as compared with daughters among Indian children below 5 years of age; further exploration of our data showed that male children consumed a higher %TEI‐NBF from healthy snacks than female children, particularly dairy‐based snacks. No studies exploring sex differentials in feeding of USFB to infants and young children have been identified.…”
Section: Discussionsupporting
confidence: 49%
“…Ordinal logistic regression model for high consumption a of unhealthy snack foods and beverages (comparison with low/moderate consumption b ) CI: confidence interval.The greater odds of high USFB consumption among female children and lower odds among children from upper caste households has not been reported elsewhere; these results indicate that sociocultural beliefs may be influencing diets of young children in Nepal.Although inequitable intra-household food allocation by sex has been noted in South Asian contexts including Nepal,(Harris-Fry, Shrestha, Costello, & Saville, 2017), literature on the influence of child sex and feeding of USFB is extremely limited Fledderjohann et al (2014). …”
mentioning
confidence: 99%
“…Female infant and child mortality are markedly higher than male mortality (Collaborators, 2010). Girls in India also experience lower access to health services (Khera et al, 2014), lower rates of immunization (Borooah, 2004;Singh, 2012), and worse performance on the proximal indicators of nutritional status, such as breastfeeding (Fledderjohann et al, 2014) as well as feeding practices and household allocation of resources towards children (Basu, 1993;Borooah, 2004;Haddad, Pena, Nishida, Quisumbing, & Slack, 1996). Discrimination in terms of care, access to health services, or other health inputs would influence nutritional status as these are key determinants of undernutrition (Black et al, 2013b).…”
Section: No Female Disadvantage In Height In Childhoodmentioning
confidence: 99%
“…Empirical research shows however that a pro-male bias in actual food intake is mainly located in South Asia, and that the extent of gender bias in nutritional status varies strongly within the region (Haddad et al 1996). Other studies show that women's nutritional status also lags behind because of differential care giving practices and lesser access to formal healthcare (Larme 1997;DeRose et al 2000;Marcoux 2002;Fledderjohann et al, 2014). Thus, the evidence of previous research on the negative effects of gender on nutrition is inconclusive.…”
Section: Introductionmentioning
confidence: 99%